Outcomes of low-intensity biopsy surveillance for rejection in paediatric cardiac transplantation. (17th June 2019) - Evers, Patrick D.; Jorgensen, Neal; Hong, Borah; Albers, Erin; Kemna, Mariska; Friedland-Little, Josh; Boucek, Robert J.; Law, Yuk
Abstract: Background: Significant inter-centre variability in the intensity of endomyocardial biopsy surveillance for rejection following paediatric cardiac transplantation has been reported. Our aim was to determine if low-intensity biopsy surveillance with two scheduled biopsies in the first year would produce outcomes similar to published registry outcomes. Methods: A retrospective study of paediatric recipients transplanted between 2008 and 2014 using a low-intensity biopsy protocol consisting of two surveillance biopsies at 3 and 12–13 months in the first post-transplant year, then annually thereafter. Additional biopsies were performed based on echocardiographic and clinical surveillance. Excluded were recipients that were re-transplanted or multi-organ transplanted or were followed at another institution. Results: A total of 81 recipients in the first 13 months after transplant underwent an average of 2 (SD ± 1.3) biopsies, 24 ± 6.8 echocardiograms, and 17 ± 4.4 clinic visits per recipient. During the 13-month period, 19 recipients had 24 treated rejection episodes, with the first at an average of 2.8 months post-transplant. The 3-, 12-, 36-, and 60-month conditional on discharge graft survival were 100%, 98.8%, 98.8%, and 90.4%, respectively, comparable to reported figures in major paediatric registries. At a mean follow-up of 4.7 ± 2.1 years, four patients (4.9%) developed cardiac allograft vasculopathy, three (3.7%) developed a malignancy, and seven (8.6%) suffered graft loss. Conclusion: Rejection surveillance with a low-intensity biopsy protocol demonstrated similar intermediate-term outcomes and safety measures as international registries up to 5 years post-transplant.